Audit Sistem Informasi Perpustakaan Sekolah Menggunakan Frame Work Cobit 5 Pada SMK Negeri 1 Sirapit - Tiara Br Bangun; Amysa Putri Sitepu; Ayuri Nirvananda; Adelia Revina Br PA (International Forum of Researchers and Lecturers, 2024)
Students, teachers, and school employees feel the impact of standardization at SMK in all related activities. The library information system must comply with the Standard Operating Procedures (SOP) established in SOP ISO 9001:2000. The current library information system has never been audited, and it is unclear whether it has helped achieve the school's vision and mission. An audit of the library information system at the Private High School (SMK) NEGERI 1 SIRAPIT is necessary to have a method to control and ensure that the library information system meets the organization's goals. Using the COBIT 5 framework and the Delivery, Service, and Support (DSS) domain, which includes DSS.1, DSS.5, DSS.11, DSS.12, and DSS.13, the library information system was audited. The research results show that one process, DSS02, has a capability level of 4, and five other processes, DSS01, DSS03, DSS04, and DSS05, each have a capability level of 4. While the overall capability level obtained based on the overall average is 3, this indicates that most tasks have been completed in the DSS domain for the library information system at SMK NEGERI 1 SIRAPIT However, there are standards established to carry out these processes, all of which are well documented and communicated. This study, which assesses the capability level of the Library Information System at SMK NEGERI 1 SIRAPIT, can contribute to the development of specific business processes if, in the future, there will be more customer services with various library service products. This can be done within the framework of the COBIT 5 audit.